Improved Function After Deep Brain Stimulation for Chronic, Severe Traumatic Brain Injury. Issue 2 (1st August 2016) - Rezai, Ali R.; Sederberg, Per B.; Bogner, Jennifer; Nielson, Dylan M.; Zhang, Jun; Mysiw, W. Jerry; Knopp, Michael V.; Corrigan, John D.
Abstract: BACKGROUND: Severe traumatic brain injury (TBI) damages the frontal lobes and connecting networks, which impairs executive functions, including the ability to self-regulate. Despite significant disabling effects, there are few treatment options in the chronic phase after injury. OBJECTIVE: To investigate the safety and potential effectiveness of deep brain stimulation (DBS) for individuals with chronic, disabling TBI and problems of behavioral and emotional self-regulation. METHODS: This study was an open-label, prospective design with serial assessments of behavioral outcomes and positron emission tomography 2 years after DBS implantation. Four participants 6 to 21 years after severe TBIs from automobile crashes were included. Although alert and volitional, all experienced significant executive impairments, including either impulsivity or reduced initiation. DBS implants were placed bilaterally in the nucleus accumbens and anterior limb of the internal capsule to modulate the prefrontal cortex. RESULTS: The procedure was safe, and all participants had improved functional outcomes. Two years after implantation, 3 met a priori criteria for improvement on the Mayo-Portland Adaptability Inventory-4. Improvement was due largely to better emotional adjustment, although 1 participant showed marked increases in multiple domains. Significant improvement in a composite score of functional capacity indicated improved independence in self-care and activities of daily living. The pattern of change in cognition corresponded with changes in activation of the prefrontal cortex observed in serial scanning. CONCLUSION: This first study of DBS to this target for severe TBI supports its safety and suggests potential effectiveness to improve function years after injury. The primary impact was on behavioral and emotional adjustment, which in turn improved functional independence. : Supplemental Digital Content is Available in the Text. Direct URL citations appear in the printed text and are provided in the HTML and PDF versions of this article on the journal's Web site (www.neurosurgery-online.com ).